2015
DOI: 10.1093/infdis/jiv433
|View full text |Cite
|
Sign up to set email alerts
|

Continued Slow Decay of the Residual Plasma Viremia Level in HIV-1Infected Adults Receiving Long-term Antiretroviral Therapy

Abstract: We measured plasma human immunodeficiency virus type 1 (HIV-1) RNA levels by means of single-copy assay in 334 participants receiving virologically suppressive antiretroviral therapy (ART). A residual viremia load of ≥1 copy/mL after 4 years of ART was predicted by a higher pre-ART HIV-1 RNA level, higher CD8 + T-cell count during treatment, and a lower ratio of CD4+ T cells to CD8+ T cells during treatment but not by initial ART regimen. In a longitudinal subset of 64 individuals, continued decay of the plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
52
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 15 publications
(25 reference statements)
5
52
1
Order By: Relevance
“…This half-life is similar to the recently reported decay of plasma HIV-1 RNA (measured by single copy assay) that continues after 4–11 years of ART (half-life 11.5 years [3]) but is longer than estimates of the half-life for cells with inducible, replication-competent virus (3.7 years; 95% CI 2.3–9.5 years) [38; 39]. These findings indicate that HIV-1-infected cell populations, including those producing virions, do not persist indefinitely and that effort should be directed toward accelerating the inherent slow decay of such cells.…”
Section: Discussionsupporting
confidence: 87%
“…This half-life is similar to the recently reported decay of plasma HIV-1 RNA (measured by single copy assay) that continues after 4–11 years of ART (half-life 11.5 years [3]) but is longer than estimates of the half-life for cells with inducible, replication-competent virus (3.7 years; 95% CI 2.3–9.5 years) [38; 39]. These findings indicate that HIV-1-infected cell populations, including those producing virions, do not persist indefinitely and that effort should be directed toward accelerating the inherent slow decay of such cells.…”
Section: Discussionsupporting
confidence: 87%
“…As these cells are eliminated, viremia declines more slowly, and additional phases of decay can be detected. After 3 to 4 years of continuous cART, viral RNA levels remain relatively stable, although Mellors and colleagues recently detected ongoing decay of HIV viremia over time (33).…”
Section: Integration: a Central Event In Retrovirus Replicationmentioning
confidence: 99%
“…Despite the study's outstanding methods and the novelty of its results, the conclusions of Lorenzo‐Redondo et al () must be taken with caution as other scientists (Kearney et al , ; Riddler et al , ; Simonetti et al , ) have not found signs of viral evolution. As the valuable data obtained in the Lorenzo‐Redondo et al () study may stimulate larger clinical studies to assess the impact on HIV reservoirs after increased cART concentrations in lymph nodes, the basis for the development of better therapeutic options will arise from more conclusive evidence.…”
mentioning
confidence: 99%
“…Although, nowadays, combined antiretroviral treatment (cART) is effective at suppressing viral replication to below the detection limits of plasma HIV‐1 RNA assays, it is not yet considered a curative therapy, because HIV‐1 continues to replicate in the so‐called viral reservoirs (Barouch and Deeks, ; Sahu, ; Riddler et al , ). Treated HIV patients need to continue lifelong therapy; otherwise, after stopping therapy, most patients will experience a rebound in plasma virus (Kearney et al , ).…”
mentioning
confidence: 99%
See 1 more Smart Citation